2014
DOI: 10.1097/aco.0000000000000045
|View full text |Cite
|
Sign up to set email alerts
|

Predicting postoperative pulmonary complications

Abstract: PPCs are associated with a higher incidence of life-threatening events and higher costs. Reliable PPC risk-stratification tools are essential for guiding clinical decision-making in the perioperative period. The care team can act on modifiable factors and optimize vigilance over nonmodifiable ones. It would be useful to focus resources on determining whether low-cost preemptive interventions improve outcomes satisfactorily or new strategies need to be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(110 citation statements)
references
References 69 publications
4
99
0
7
Order By: Relevance
“…Sabaté et al[24] examined the implications of postoperative pulmonary complications and reported an increased incidence of mortality, length of stay, readmissions, and costs. Our case series gives a limited account of the clinical progression of the patients as well as long term follow up examining the clinical sequelae of their complication.…”
Section: Discussionmentioning
confidence: 99%
“…Sabaté et al[24] examined the implications of postoperative pulmonary complications and reported an increased incidence of mortality, length of stay, readmissions, and costs. Our case series gives a limited account of the clinical progression of the patients as well as long term follow up examining the clinical sequelae of their complication.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Especially, the postoperative pulmonary complication rates after abdominal surgery were reported to range between 10% and 80%, depending on the definition of the complications. [13] In our study, to appropriately reflect the clinical significance, the definition of postoperative pulmonary complications included clinical manifestations such as productive cough, atelectasis, and pleural effusion, which did not necessarily require interventions such as chest tube insertion. In addition, the characteristics of the study population such as age, body mass index, and comorbidities were dissimilar to the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 These postoperative complications contribute to the risk of surgery, especially cardiothoracic and abdominal-wall surgery. 33 The incidence is higher for patients undergoing thoracic surgery (19 -59%) than for those undergoing upper (16 -20%) or lower (0 -5%) abdominal surgery.…”
Section: Postoperative Adult and Pediatric Patientsmentioning
confidence: 99%